Kierkegaard and the paradox of religious diversity - Connell, George B. 1957- (Grand Rapids, Michigan Cambridge, U.K. William B. Eerdmans Publishing Company, 2016)
Pagans and Jews: Kierkegaard's religious others -- Truth and religious pluralism -- Transposing transgression: reading fear and trembling through Danish film -- Religion and religions: Kierkegaard and the concept of religion -- Kierkegaard and Confucius: the religious dimensions of ethical selfhood
Pagans and Jews: Kierkegaard's religious othersTruth and religious pluralism -- Transposing transgression: reading fear and trembling through Danish film -- Religion and religions: Kierkegaard and the concept of religion -- Kierkegaard and Confucius: the religious dimensions of ethical selfhood.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Kierkegaard, Søren 1813-1855; Kierkegaard, Søren -- 1813-1855; Cultural Pluralism -- Religious aspects; Religions; Religious Pluralism; Cultural Pluralism -- Religious aspects; Christianity and other religions